2012
DOI: 10.4103/0972-6748.119604
|View full text |Cite
|
Sign up to set email alerts
|

Internal predictors of burnout in psychiatric nurses: An Indian study

Abstract: Background:Research has not adequately focused on the issue of burnout in Psychiatric nurses, despite the fact that they suffer considerable stress in their work. Till date no study has been conducted on burnout among psychiatric nurses in India. Further, there is a particular lack of research in internal variables predicting burnout in them.Aims:To determine whether there are any internal psychological factors relevant to burnout in psychiatric nurses in India.Materials and Methods:We recruited 101 psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This finding agrees with the results of many previous studies that have highlighted that nurses belong to a category of workers who are more susceptible to burnout because they are in continuous contact with emotions related to patients and their diseases (Borritz et al, 2006;Chakraborty, Chatterjee, & Chaudhury, 2012;Koch, Stranzinger, Nienhaus, & Kozak, 2015). In other studies, statistically significant associations were observed between emotional exhaustion, depersonalization and job performance and emotional exhaustion was emphasized as the dominant factor that was associated with greater decreases in job performance (Bartram, Casimir, Djurkovic, Leggat, & Stanton, 2012…”
Section: T a B L E 1 Sample Characteristicssupporting
confidence: 91%
“…This finding agrees with the results of many previous studies that have highlighted that nurses belong to a category of workers who are more susceptible to burnout because they are in continuous contact with emotions related to patients and their diseases (Borritz et al, 2006;Chakraborty, Chatterjee, & Chaudhury, 2012;Koch, Stranzinger, Nienhaus, & Kozak, 2015). In other studies, statistically significant associations were observed between emotional exhaustion, depersonalization and job performance and emotional exhaustion was emphasized as the dominant factor that was associated with greater decreases in job performance (Bartram, Casimir, Djurkovic, Leggat, & Stanton, 2012…”
Section: T a B L E 1 Sample Characteristicssupporting
confidence: 91%
“… 8 Chakraborty et al found no significant correlation between the level of burnout and rank. 16 A previous meta-analysis conducted using the literature originating from the USA showed that the correlation between burnout and years of experience is inconclusive. 30 It may be necessary to investigate this potential relationship further, especially within the local context.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The CBI has been used in both general and psychiatric nursing studies and has also been validated in a general South African occupational group. 16 , 24 , 25 All items are rated on a five-point Likert scale ranging from 1 (never or almost never) to 5 (always). Responses for each question are given scores between 0 and 100.…”
Section: Methodsmentioning
confidence: 99%
“…Two Indian studies relating to medical profession used CBI – one in residents in a tertiary hospital[ 21 ] and another in psychiatric nurses. [ 22 ] The consequences of BS can be devastating – higher suicide rates than those of the general population and higher rates of divorce and substance abuse compared with other physicians and nonphysicians. [ 23 ] These should make the profession alert.…”
Section: Discussionmentioning
confidence: 99%